Inflammatory Markers and Incidence of other Autoimmune Diseases in Patients with Oral Lichen Planus - Ana Družijanić; Ana Glavina; Mirna Draganja; Dolores Biočina-Lukenda; Livia Cigić (University of Zagreb. School of Dental Medicine, 2019)
Introduction: Oral lichen planus (OLP) is a chronic immune, inflammatory disease of the oral cavity of a still unknown etiology. Materials and methods: The study involved 63 subjects diagnosed with oral lichen planus and 63 subjects without pathologic changes in the oral mucosa who were classified as controls. All subjects were given a detailed medical history at first screening. The medical history of the presence of other autoimmune disease in all subjects was supported by medical records. A sample of venous blood was taken from each subject in order to determine sedimentation rate (SE) and leukocyte count (L) using standard laboratory procedures, and serum C-reactive protein (CRP) concentration values were determined as well. Statistical analysis: The methods of descriptive statistics, χ2-test, the Fisher's exact test, and the Student's t-test were used in the statistical processing of the results. The results were interpreted at a significance level of P <0.05. Results: For all three measured inflammatory markers, there were no statistically significant differences in the number of subjects with elevated values between the test and control groups (P = 0.364 for SE; P = 1.000 for CRP and P = 0.219 for L). The prevalence of other autoimmune disease in the OLP group was higher than in the control group, with statistical significance, and the most common was cutaneous lichen in nine subjects (14.29%) with OLP and celiac disease seven subjects (11.11%). Conclusions: The results showed that there was no significant difference in the average values of the investigated inflammatory markers in blood (SE, CRP and L) between patients with OLP and control subjects, while a significantly higher incidence of other autoimmune diseases in patients with OLP was demonstrated.